2014
DOI: 10.1021/jp506689n
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport through Carbon Nanomembranes

Abstract: Molecular junctions incorporating pristine and cross-linked aromatic self-assembled monolayers (SAMs) are fabricated and investigated. A two-terminal setup composed of a eutectic Ga–In (EGaIn) top electrode and the gold substrate on which SAMs are prepared as a bottom electrode was used to characterize the charge transport. SAMs of phenylthiol (PT), biphenylthiol (BPT), p-terphenylthiol (TPT), and p-quaterphenylthiol (QPT) are then irradiated with low-energy electrons and converted into carbon nanomembranes (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 60 publications
9
28
1
Order By: Relevance
“…It has been suggested that molecular junctions can be seen as “series tunneling junctions” where each molecular component forms a distinct part of the tunnel junction. According to this view of molecular junctions, here, the alkyl chain and BPh units pose two distinct tunneling barriers in series where the tunneling barrier widths are defined by the lengths of the alkyl chain (which depends on n ), d alk , and the BPh unit, d BPh , and tunneling barrier heights are defined by the alkyl chain, φ alk , and BPh unit, φ BPh (Figure c). Thus, in principle, the junctions are double-barrier junctions with the corresponding tunneling decay coefficients along the alkyl chain, β alk , and BPh units, β BPh , given by eq In general, the aromatic part poses a lower φ than the aliphatic molecules (as indicated in Figure c); consequently, aromatic molecules have typical values of β in the range of 0.2–0.4 Å –1 , whereas aliphatic molecules have β of 0.8 Å –1 . In addition, others have suggested that intermolecular tunneling (where charges tunnel from one molecule to another) may be important for molecules with large tilt angles. In case the double-barrier picture holds, the tunneling rates are determined by the BPh units for small values of n , and the red arrows in Figure a indicate that the tunneling direction should be determined by the tilt angle of the BPh units, which, in turn, should influence the directional plasmon launching as indicated by the blue arrows.…”
mentioning
confidence: 99%
“…It has been suggested that molecular junctions can be seen as “series tunneling junctions” where each molecular component forms a distinct part of the tunnel junction. According to this view of molecular junctions, here, the alkyl chain and BPh units pose two distinct tunneling barriers in series where the tunneling barrier widths are defined by the lengths of the alkyl chain (which depends on n ), d alk , and the BPh unit, d BPh , and tunneling barrier heights are defined by the alkyl chain, φ alk , and BPh unit, φ BPh (Figure c). Thus, in principle, the junctions are double-barrier junctions with the corresponding tunneling decay coefficients along the alkyl chain, β alk , and BPh units, β BPh , given by eq In general, the aromatic part poses a lower φ than the aliphatic molecules (as indicated in Figure c); consequently, aromatic molecules have typical values of β in the range of 0.2–0.4 Å –1 , whereas aliphatic molecules have β of 0.8 Å –1 . In addition, others have suggested that intermolecular tunneling (where charges tunnel from one molecule to another) may be important for molecules with large tilt angles. In case the double-barrier picture holds, the tunneling rates are determined by the BPh units for small values of n , and the red arrows in Figure a indicate that the tunneling direction should be determined by the tilt angle of the BPh units, which, in turn, should influence the directional plasmon launching as indicated by the blue arrows.…”
mentioning
confidence: 99%
“…SAMs also cannot grow on top of each other, so their layer thickness is limited to the length of a molecule (typically 1–2 nm). To overcome these limits, we utilize carbon nanomembranes (CNMs) from cross-linked aromatic SAMs via electron irradiation. The underlying mechanisms of cross-linking have been investigated using different surface-sensitive analytical techniques. The electronic transport through CNMs was studied by conductive probe atomic force microscope and eutectic Ga–In top contacts, , which demonstrates the potential of CNMs for use as a dielectric material. Recently, CNMs prepared from p -terphenylthiol were found to possess a high permeance and selectivity particularly for water molecules due to the presence of subnanometer channels .…”
mentioning
confidence: 99%
“…15−17 The underlying mechanisms of cross-linking have been investigated using different surface-sensitive analytical techniques. 18−21 The electronic transport through CNMs was studied by conductive probe atomic force microscope and eutectic Ga−In top contacts, 22,23 which demonstrates the potential of CNMs for use as a dielectric material. Recently, CNMs prepared from pterphenylthiol were found to possess a high permeance and selectivity particularly for water molecules due to the presence of subnanometer channels.…”
mentioning
confidence: 99%
“…In the first growth step, Figure a (i), 4-(4-thiophenyl)­pyridine (TPP) (b), 4-(1 H -pyrrole-1-yl)­thiophenol (PTP) (c), or 4-(2,5-dimethyl-1 H -pyrrole-1-yl)­thiophenol (DPTP) (d) compounds form a SAM on a copper substrate by vapor deposition (VD) under vacuum. In the second step, Figure a (ii), low-energy electron irradiation induced cross-linking converts the SAM into a molecular nanosheet: a carbon nanomembrane (CNM). CNMs have been fabricated from different molecules, and their structure and mechanical, optical, and electrical behavior can be engineered in this way. The vacuum pyrolysis results in their conversion into graphene. , For the N-containing molecules (TPP, PTP, DPTP, Figure b) investigated in this study, we show that for a low pyrolysis temperature T p 1 nitrogen-doped nanocrystalline graphene is formed, Figure a (iii). By increasing the temperature to T p 2 , the recrystallization of the graphene sheet leads to the formation of nanopores by extrusion of the nitrogen atoms, Figure a (iv).…”
mentioning
confidence: 74%